2012
DOI: 10.1039/c2jm34111e
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up/top-down synthesis of stable zirconium hydroxide nanophases

Abstract: It is well known that the structure of ZrO 2 powder synthesized by low temperature calcination of hydrous zirconia is strongly affected by the nature and properties of precursors. In the present paper, we combined a precipitation/restructuring approach (bottom-up/top-down methodology) to produce zirconium hydroxide nanoparticles that transform into stable nanophasic tetragonal zirconia by low temperature calcination. The dimension and structure of precursors could be modulated by adjusting pH. The synthetic ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The XRD pattern showed that the powders from the treatment at 100 C exhibit broad diffraction peaks similar to (i) X-ray amorphous zirconium patterns, or (ii) structures with extremely small dimensions. 30 On the other hand, the XRD pattern of the samples obtained by hydrothermal treatment at 150 C and 200 C shows well dened peaks, which can be assigned as the tetragonal or cubic phases for the ZrO 2 nanostructure in both samples. 31 It is well known that the tetragonal and cubic phases for the ZrO 2 are very similar and both show a diffraction peak around 2q ¼ 30 (111).…”
Section: Resultsmentioning
confidence: 92%
“…The XRD pattern showed that the powders from the treatment at 100 C exhibit broad diffraction peaks similar to (i) X-ray amorphous zirconium patterns, or (ii) structures with extremely small dimensions. 30 On the other hand, the XRD pattern of the samples obtained by hydrothermal treatment at 150 C and 200 C shows well dened peaks, which can be assigned as the tetragonal or cubic phases for the ZrO 2 nanostructure in both samples. 31 It is well known that the tetragonal and cubic phases for the ZrO 2 are very similar and both show a diffraction peak around 2q ¼ 30 (111).…”
Section: Resultsmentioning
confidence: 92%
“…The high yield (>95%) and large scale production (40g) are two characteristic features that have made this process as state-of-the-art for nanocrystal synthesis. 104 Another study also supported that high temperature synthesis leads to the increases of the nanoparticle size due to comparatively higher reactivity of the metal complex in the solvent. 106 However, the metal oxide NPs with nanozyme activity prepared by this method are usually smaller in size, crystalline and dispersed only in the organic solvent.…”
Section: Synthesis Of Metal Oxides Nanozymesmentioning
confidence: 88%
“…The bottom-up approach mostly includes processes such as sol-gel, reverse micelle, chemical vaour deposition (CVD), pyrolysis, biosynthesis, microwave-assisted, and flow synthesis, and most of these processes refer to as wet chemical synthesis. [103][104][105] In the following sections, we highlight the synthesis of metal oxide, metallic and carbon-based nanozymes with different size, shape and morphology using top-down and bottom-up approaches.…”
Section: Synthesis Of Common Nanozymes Used In Electrochemical Biosensorsmentioning
confidence: 99%
“…The phase composition of the catalysts reduced at 350 • C was analyzed by X-ray powder diffraction (Figure 3). In the XRD diffractogram of the ZrO 2 support, we observed a broad peak at 2θ ∼ = 30 • and a second, lower-intensity peak at 2θ ∼ = 50 • ; these diffractions were ascribed to the amorphous ZrO 2 [44][45][46][47][48]. The addition of Au ensembles to the amorphous ZrO 2 support showed sharp peaks at 2θ = 30.3, 35.3, 50.3 and 60.1 • ; these peaks were attributed to the crystallization of the amorphous ZrO 2 support, i.e., the phase transformation of the amorphous to the tetragonal phase of ZrO 2 (JCPDS card 01-080-0784).…”
Section: N 2 Physisorption Au Loadingmentioning
confidence: 82%